Resources Influence Retirement and Life Satisfaction - Mary, Pang,; Ming, Lai, Ming; Lee, Chong, Lee (International Journal of Engineering and Technology, 2018)
Retirement is a one’s of life essential transition. To maintain a positive well-being have become major concerns for individuals, organizations, and governments. Retirement has the potential to be a challenging transition in late adulthood, often causing instability in financial, emotional, health and social resources. This paper is motivated to examine the relationships between resources, life satisfaction and retirement satisfaction of retirees in Malaysia. We used purposive sampling method and personally administered 55 retirees. The correlation and regression results indicated that financial, physical health and emotional resources had positive relationships with life satisfaction. Likewise, cognitive and motivation resources have positive relationships with retirement satisfaction.